Improvement Of Caregivers Ability to Care for Patients in Mentari Hati Social Institutions Tasikmalaya - Neni Sholihat; Indra Gunawan; Nia Restiana; Rosy Rosnawanty; Saryomo Saryomo (AbdimasMu UMTAS, 2022)
Based on Riskedas data in 2013, the prevalence of mental disorders in Indonesia is about 6% of the population has emotional disorders and 1.7% of serious mental disorders. In West Java the prevalence reaches 1.6%, while in Tasikmalaya City there are 171 sufferers. Mental disorders can be caused by biological, psychological and socio-cultural factors, it can also be caused by inadequate provision of patient care, especially in small towns and villages. Patients with chronic mental disorders need care management that involves various elements in the healing process, such as family, community and caregivers. The role of care giver which is very influential in the patient's healing process, they are in charge of providing emotional support and the necessities of life. The complex problems in patient care caused many of them not to be well cared for. One of the phenomena was found at the Mentari Hati Social Institusion. The caregiver's low educational background, and lack of knowledge in care, are among the factors causing the ineffective treatment provided. For this reason, a mental nursing service management program is needed which is managed in a Community Mental Health Nursing (CMHN) program which aims to empower caregivers by providing consultation and education services, and providing information on mental health principles. The purpose of this community service activity is to improve the care giver's ability to care for mental patients.